Happy ever after - Adler, Peter 1933- (Manchester University Press, 2024)
"Peter Adler was born in April 1933 in Berlin. When Hitler came to power, his father lost his job for being Jewish, and in 1936 he moved to England, where he had to requalify as a doctor. By June 1938, Peter, his mother and sisters had joined his father in London and during the Blitz, Peter was evacuated to the countryside. After studying medicine at London University, Peter met with his wife Eve, a nurse. They moved to Zambia for two years, lived in Israel for a short period, and settled in Luton where Peter worked as a doctor in a general practice. They have three daughters, Keren, Tami and Mandy. Peter and Eve now live in Derby and enjoy spending time with their children and grandchildren."
Keywords: Adler, Peter -- 1933-; Autobiografie